Evaluation of Soil Stabilization from Marble Ash Powder and Asphalt Emulsion as Supporting Soil for Logistics Buildings - Meita Simanjuntak; Putty Maura Amalia; Geni Firuliadhim; Syahril Syahril (Potensi: Jurnal Sipil Politeknik, 2024)
This research focuses on improving the bearing capacity of soil by applying soil stabilization methods. Specifically, this research explores the use of a mixture of marble powder ash and emulsified asphalt to improve soil physical properties and increase soil bearing capacity to support logistics buildings such as lime or rice storage warehouses. This research was conducted in Cililin area which has soft clay soil that is unsuitable for construction. Tests were conducted in the laboratory using various compositions of marble dust ash (0%; 2.5%; 5%; 7.5%; 10%) and 6% emulsified asphalt. The tests measure the CBR (California Bearing Ratio) and UCS (Unconfined Compressive Strength) values of the soil. The tests measured the CBR (California Bearing Ratio) and UCS (Unconfined Compressive Strength) values of the soil. The test results showed a direct relationship between increasing marble ash composition with CBR and UCS values, with the highest design CBR value in the unsoaked method being 8% and the maximum qu value being 1.676 kg/cm². However, the desired CBR value of >10% was not achieved in this study. To fulfill this requirement, future studies should consider compositions higher than 10% and for better results can use asphalt emulsion of more than 6%.